Interpretação do patrimônio geológico do Rio Uru em Heitoraí (GO) aplicada ao geoturismo - Morais, Márcio José Pires de (2022)
Geodiversity was the theme of this dissertation, as it studies the abiotic nature that is constituted by a diversity of geological, geomorphological, water, fossil, soil and other surface deposits that favor the development of life on Earth, having as intrinsic values culture, aesthetics, economics, scientific, geoeducational and geotourism. The main objective of this research was based on the interpretation of the geological heritage of the Uru River, in the “Desertor” area, in the municipality of Heitoraí / GO, where 10 geopoints with potential for geotourism were listed. The studies were based on Geodiversity, Geological Heritage, Geoconservation, Geotourism and Geoeducation with a view to local sustainable socio-environmental development and also to focus on the possibility of generating income for the people. To this end, the research paths went through the bibliographic survey, field work with photographic records, notes in a notebook, collection of reports in minutes and public meetings with the Association of Residents of Rio Uru, in addition to capturing and elaborating cartographic materials in the periods from 2021 to 2022. The landscape changes are alarming along the banks of the River Uru and adjacent to the implementation of basic infrastructure to service the 5 condominiums already installed and other residences and farms that are being installed. It is worth mentioning that the project “Descida Ecológica do Rio Uru” fulfills its geoeducational, geoconservationist and environmental education role, strengthening the initial guidelines for future geotourism practices.